U3-1402 sensitizes HER3-expressing tumors to PD-1 blockade by immune activation - Haratani, Koji; Yonesaka, Kimio; Takamura, Shiki; Maenishi, Osamu; Kato, Ryoji; Takegawa, Naoki; Kawakami, Hisato; Tanaka, Kaoru; Hayashi, Hidetoshi; Takeda, Masayuki; Maeda, Naoyuki; Kagari, Takashi; et al. (The Journal of clinical investigation, 2020)
Immunotherapy targeting programmed cell death-1 (PD-1) induces durable antitumor efficacy in many types of cancer. However, such clinical benefit is limited because of the insufficient reinvigoration of antitumor immunity with the drug alone; therefore, rational therapeutic combinations are required to improve its efficacy. In our preclinical study, we evaluated the antitumor effect of U3-1402, a human epidermal growth factor receptor 3-targeting (HER3-targeting) antibody-drug conjugate, and its potential synergism with PD-1 inhibition. Using a syngeneic mouse tumor model that is refractory to anti-PD-1 therapy, we found that treatment with U3-1402 exhibited an obvious antitumor effect via direct lysis of tumor cells. Disruption of tumor cells by U3-1402 enhanced the infiltration of innate and adaptive immune cells. Chemotherapy with exatecan derivative (Dxd, the drug payload of U3-1402) revealed that the enhanced antitumor immunity produced by U3-1402 was associated with the induction of alarmins, including high-mobility group box-1 (HMGB-1), via tumor-specific cytotoxicity. Notably, U3-1402 significantly sensitized the tumor to PD-1 blockade, as a combination of U3-1402 and the PD-1 inhibitor significantly enhanced antitumor immunity. Further, clinical analyses indicated that tumor-specific HER3 expression was frequently observed in patients with PD-1 inhibitor-resistant solid tumors. Overall, U3-1402 is a promising candidate as a partner of immunotherapy for such patients.